Comprehensive Risk Analysis in Entrepreneurship in Times of Crisis - Revelo-Rosero, Jorge Enrique (2020)
The objective of this study is to identify and analyze the potential market, operational and competitive risks faced by the startups in times of crisis. Comprehensive management of risk in entrepreneurship, today, is a priority for entrepreneurs who have the need to achieve independence and economic stability. The research was of a non experimental descriptive type with a qualitative approach through the application of an interview structure of 24 questions addressed to 15 managers and / or business owners considered as undertakings in the city of Quito, without discriminating gender or type of business. The results obtained from the interview served as the basis for developing a risk matrix to generate valid recommendations on how to mitigate the risks that may arise when developing new startups in times of crisis.